PERAN ETIKA PENETAPAN HARGA TERHADAP KEPUASAN KONSUMEN DALAM LAYANAN HOMESTAY - M Soleh Mauludin; Zakiyatus Soimah; Ditha Dwi Putri; Dewi Azizah Nawang Sari; Rahma Hanik Alawiyah; Ninda Rahayu Salsabilah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This study aims to deeply understand the role of pricing ethics on consumer satisfaction in homestay services, with a case study focus on Homestay Delila on Jl. Sunan Drajat, Kediri. Using a qualitative approach, this study seeks to explore the perspectives and experiences of consumers and homestay owners regarding pricing practices that are considered ethical and their impact on satisfaction levels. The concept of price and consumer satisfaction serves as the theoretical basis for analyzing data collected through in-depth interviews and observations. The results of the study provide a comprehensive picture of how transparency, fairness, and honesty in pricing affect perceptions of value and ultimately shape homestay consumer satisfaction. The practical implications of this study are useful for homestay business actors to develop more ethical pricing strategies to increase consumer loyalty and recommendations.